Politics and professionalism in community development: Examining intervention in the highlands of northern Thailand - Mckinnon, Katharine Islay (Massey University, 2009)
It has been suggested that the practice of international development assistance is so deeply problematic that the only moral choice is to abandon the work altogether. The practice of community development in the Third World has been the subject of extensive critique for several decades. Scholars and development practitioners speak of the 'tyranny' of development and discuss the ways in which development is a means of control and domination rather than an altruistic enterprise whereby wealthier nations lend assistance to poorer nations. How are these debates relevant to highland development programs in northern Thailand? And how are development practitioners responding to the suggestion that they are making things worse rather than better? This paper explores the history of development in the hills and suggests some ways that development practitioners can - and do - take on board recent critiques of development while continuing to work for the betterment of highland lives and livelihoods.
Keywords: Fields of Research::360000 Policy and Political Science::360200 Policy and Administration::360201 Public policy